Extraction and Bioactivity Analysis of Major Flavones Compounds from Scutellaria baicalensis Using In Vitro Assay and Online Screening HPLC-ABTS System - Kwang Jin Lee; Pil Mun Jung; You-Chang Oh; Na-Young Song; Taesoo Kim; Jin Yeul Ma (Journal of Analytical Methods in Chemistry)
The extraction efficiency of a number of solvent compositions for the improvement of bioactive compounds yield from S. baicalensis has been investigated. Also, free radical scavengers in the glycoside baicalin (BG), wogonoside (WG), aglycon baicalein (B), and wogonin (W) compounds of S. baicalensis were screened, identified, and quantified using coupled offline ABTS and online screening HPLC-ABTS assay. Increasing ethanol content fractions resulted in decreased extract yield of bioactive compounds. In this case, the best yield of 37.01 mg/g in BG, WG, B, and W compounds was obtained by a dipping method with an extraction time of 4 h. In addition, the yield (43.05%) and IC50 (34.04 μg/mL) determined through ABTS assay of the 60% aqueous ethanol extract were the most satisfactory of all solvent solutions tested. This result shows that an online screening HPLC-ABTS assay can be a powerful technique for the rapid characterization of bioactivity compounds in plant extracts. Moreover, their anti-inflammatory activities were evaluated via analyzed inhibitory effect on NO and inflammatory cytokine production. Furthermore, WG and W exhibited the strong inhibitory effects on inflammatory mediator production including NO, IL-6, and IL-1β in LPS-stimulated RAW 264.7 macrophages.